2009
DOI: 10.3758/app.71.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical interaction of sex and expression in face classification tasks

Abstract: Classification of faces as to their sex or their expression-with sex and expression varying orthogonally-was studied in three experiments. In Experiment 1, expression classification was influenced by sex, with angry male faces being classified faster than angry female faces. Complementarily, sex classification was faster for happy than for angry female faces. In Experiment 2, mutual interaction of sex and expression was also found when the participants were asked to classify top and bottom face segments. In Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 63 publications
12
70
1
Order By: Relevance
“…One possible reason for this discrepancy might be due to the fact that we used faces showing happy or angry expressions, instead of non-expressive faces. Previous studies that have shown an interaction between expression and gender in face classification tasks indicate that the expression shown by the face can influence speed and accuracy of gender identification (Aguado et al, 2009). It might well be that the effects of SF content on gender classification are also different for expressive and neutral faces.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One possible reason for this discrepancy might be due to the fact that we used faces showing happy or angry expressions, instead of non-expressive faces. Previous studies that have shown an interaction between expression and gender in face classification tasks indicate that the expression shown by the face can influence speed and accuracy of gender identification (Aguado et al, 2009). It might well be that the effects of SF content on gender classification are also different for expressive and neutral faces.…”
Section: Discussionmentioning
confidence: 95%
“…Of this face set, 29 stimuli had been used in previous experiments on the interaction of gender and expression in face classification (see Aguado et al, 2009). There were 16 faces of males and 16 of females.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…Given that these facial cues are simultaneously present on the face, a growing literature has begun to investigate how these cues interact (Freeman & Ambady, 2011;Quinn & Macrae, 2011 for reviews). Of relevance to the current investigation is the finding that facial cues indicating a person's sex and race can influence perception of emotional expressions (Aguado, García-Gutierrez, & Serrano-Pedraza, 2009, Craig, Koch, & Lipp, 2017Craig, Lipp, & Mallan, 2014;Craig, Mallan, & Lipp, 2012;Hugenberg, 2005;Hugenberg & Sczesny, 2006;Lipp, Karnadewi, Craig, & Cronin, 2015).…”
mentioning
confidence: 99%
“…The teeth of the happy pictures will be blurred by using a 10-pixel Gaussian filter. To avoid differences on energy or luminance all the pictures on both tasks, we will equate the contrast energy for assessment and training [86, 89]. Furthermore, a gamma correction will be applied to the 24” BENQ LCD monitor where the stimuli will be displayed.…”
Section: Methodsmentioning
confidence: 99%